Implementation of the Principle of the Rule of Law In the Criminal Process of Ukraine under Martial Law - Khablo, Oksana; Nykonenko, Mykhailo; Zaika, Serhii; Galagan, Sergii; But, Yurii (Jurnal Cita Hukum, 2025)
The scientific article focuses on the theoretical and applied problem of applying the rule-of-law principle in the criminal process in Ukraine under martial law. It is stated that in such critical conditions for Ukraine, most elements of the rule of law are negatively affected in the form of relevant restrictions, the necessity of which is of an objective nature due to the need to prevent global threats to the independence and territorial integrity of the state, repel armed aggression, ensure national security, as well as real and potential threats to human rights and freedoms. It is emphasized that to prevent violations of constitutional rights and human liberties, the problem of combating crime and protecting human rights under special legal regimes should be solved through such interrelated components as: legislative establishment of permissible restrictions on rights; creation of a mechanism for monitoring the adoption of measures that provide for limitations on rights; activities of institutions that ensure the protection and restoration of violated rights. It is concluded that in connection with the military events in Ukraine and numerous facts of committing illegal acts, it is essential to ensure not only the effective investigation of criminal offenses, the preservation of evidence, and ensuring the proper quality of investigative (search) actions, but also compliance with the rule of law and other principles of criminal justice. This requires a comprehensive approach: improving criminal procedural legislation, involving international organizations, and enhancing the skills of justice and law enforcement officials. It is emphasized that, under such conditions, international cooperation in criminal proceedings is of great importance to Ukraine and helps improve both the regulatory framework and practical experience. It is summarized that to unconditionally bring to justice those responsible for committing war and other crimes on the territory of Ukraine, criminal proceedings must be conducted in accordance with the general standards, requirements, and procedures of international judicial institutions, which will testify to the rule of law in the country, even in conditions of forced restriction of the rights and freedoms of citizens.